School to work transition in the Resilience and Recovery Facility framework: Youth oriented active labour market policies under Pillar 6 - Simões, F. (School to work transition in the Resilience and Recovery Facility framework: Youth oriented active labour market policies under Pillar 6, 2022)
This report examines youth-oriented active labour market policies under Pillar 6 of the Resilience and Recovery Facility instrument. The report focuses on school to work transition trends for the past 10 years and in the aftermath of COVID-19. It examines the Recovery and Resilience Plans’ main features in this domain, and the Southern EU countries’ approach to active labour market policies for young people. We draw policy recommendations aiming at horizontal and vertical collaboration in the implementation of these policies or youth participation in the implementation of active labour market policies. We also specify recommendations for Southern EU countries aiming at greater coverage of vulnerable groups of young people or more thoughtful consideration of subnational disparities when implementing this type of policy measure. This document was provided by the Economic Governance Support Unit at the request of the ECON Committee.